OH FULL-FLEDGED ISLAMIC BANKS! DO YOU DISCLOSED YOUR PRODUCT DISCLOSURE SHEET? - Muhammad Fakhirin Bin Che Majid; Assoc. Prof. Dr. Muhammad Nasri Bin Md. Hussain; Dr. Suhaimi Bin Ishak (International Journal of Accounting, Finance and Business, 2020)
Product Disclosure Sheet (PDS) caught low level of awareness by the consumersregarding the availability to obtain product information and facilitate them in financialdecision making. PDS of banking product is crucial and needed by the consumer according tothe five disclosure principles which are timely, clear and concise, accurate and relevant,highlight important information, and consistent and comparable. The objective of the paper isto highlight the practice of disclosing the PDS by local owned full-fledged Islamic banks inMalaysia. The study is quantitative research and data were collected from the banks’ website.The data was analysed using SPSS. Findings revealed that all Islamic banks make the productdisclosure sheet available in their website, however, there are banks which did not disclosedthe PDS for a few of their Islamic home financing products which is BIMB and BMMB. It ishighly recommended for the Islamic banks to deliver such information in promoting bestpractices when providing services to customer without ambiguity. Survey of disclosure practiceand quality of PDS could be conducted in the area of all Islamic banks for future study tocompare the practice.